What about TEFL without Method? - Fachrurrazy, Fachrurrazy (TEFLIN Journal, 2015)
In EFLT settings CLT is now criticized due to the difficulties in its implementation. This article presents the criticisms on CLT and suggests alternative ways for TEFL, especially in Indonesia.